PENGARUH PENGAWASAN TERHADAP DISIPLIN KERJA PEGAWAI BADAN PENANGGULANGAN BENCANA DAERAH KABUPATEN BERAU - Purwoko, Agus (STIE Muhammadiyah Tanjung Redeb, 2017)
The purpose of this study is to know clearly about the influence of supervision on the discipline of employees of the Regional Disaster Management Agency of the District of Berau. This writing using analysis tools are: Product Moment correlation coefficient, simple linear regression equation and hypothesis testing with Test t.           Based on the results of the research can be seen that the simple linear regression equation on the influence of supervision on the discipline of employees of the Regional Disaster Management Agency of Berau District is Y = 7.05 + 0.76X. The value of product moment correlation coefficient is 0,9101, so r> 0 (0,9101> 0) hence there is positive linear correlation between supervisory variable and work discipline variable. In this case the close relationship between the two variables can be interpreted as very high correlation (in the scale of 0.800-1000). The value of t arithmetic is 14.90 while the value of t table is 2.0129. So that the value of t arithmetic greater than t table (14,90> 2.0129), then the hypothesis proposed in this study accepted or proved that the supervision has a significant effect on the discipline of employees of the Regional Disaster Management Agency of the District of Berau.